Analyses and optimizing of bidirectional quantum teleportation using a five-qubit cluster state as quantum channel. (1st December 2022) - Yuan, Hao; Liu, Xiang-Yuan; Pan, Guo-Zhu; Kong, Min; Zhang, Gang
Abstract: Using a five-qubit cluster state as quantum channel, a novel bidirectional quantum teleportation protocol has been proposed by Wang and Li (2022 Quantum Inf. Process. 21 44) recently in which there are two legitimate parties, Alice and Bob. Alice can teleport a two-qubit pure entangled state to Bob, simultaneously Bob can teleport a single-qubit state to Alice. In this paper, based on the same five-qubit cluster state as quantum resource, we put forward an optimized protocol. A comparison with Wang and Li's protocol is made which reveals distinct advantages of the optimized protocol in reducing the classical resources and degrading the complexity of necessary quantum operations, as well as increasing the inherent efficiency. Additionally, some mistakes in Wang and Li's protocol are pointed out and amended.